Names exist when carving begins (shi zhi you ming 始制有名): A theory of names in Daodejing (道德經) - Hong, Hao (Asian philosophy, 2024)
Naming or names (ming 名) is one of the key concepts in Daodejing (道德經). According to a popular understanding, names in Daodejing correspond to features (xing 形) of things; ordinary things have names, but Dao is featureless and nameless. What is missing, however, is atheory of the relationship between names and features explaining why ordinary things have names but Dao does not. In this paper, I develop a theory of names in Daodejing that explains how names relate to things and their features. According to this theory, a name corresponds to a feature that is shared by a group of things, and names provide identity conditions for individuating ordinary things. Further, this theory implies that the various descriptions of Dao in Daodejing do not include names; therefore, talking about Dao while insisting that it is unnamable is not committed to any paradox.